QUALIFICATION STRUCTURE OF HUMAN RESOURCES IN SPORT IN MUNICIPALITIES BIJELO POLJE, MOJKOVAC I KOLASIN - Milan Jovanović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Modern sport is featured by high competitiveness and equality in accomplishing maximum results. Sport, as a social phenomenon, consolidates cognitions from many sciences. World experiences indicate to a need for engaging professional staff with an appropriate professional qualifications. The aim of this research is to determine qualification structures in sport in three municipalities in the north of Montenegro (Bijelo Polje, Mojkovac i Kolasin). The sample consists of 88 examinees and 2 subsamples, made of 65 human resources in sport's (coaches) and 23 human resources in business function (managers). In data collecting, poll technique was used and measuring instrument was a questionnaire or poll leaflet. The questionnaire consists of 12 questions of standardized form, of personal and questions current in subject of research, so that responses give reliable information. Given results are processed, presented in tables and discussed.